Flexural behavior of concrete beams reinforced with glass fiber reinforced polymer and steel bars - Farias, Cristian; Pessi, Sarah; Wanderlind, Augusto; Piva, Jorge Henrique; Pavei, Elaine (Revista de la Construcción. Journal of Construction, 2022)
In this study, a comparative experimental analysis is performed between steel-reinforced concrete beams, which are dimensioned based on NBR 6118 (2014), and beams reinforced with glass fiber-reinforced polymer (GFRP) rebar, which are dimensioned based on ACI 440.1R (2015) after being subjected to a four-point bending test. The beams are dimensioned to resist the same force and to satisfy the service limit state (SLS). Results show that the two groups of beams exhibit similar vertical displacement behaviors until the SLS-DEF, whereas the GFRP beams exhibit larger deflections. At the ultimate load, the beams with fiberglass bars indicate a higher resistance by approximately 64% compared with those with metal bars.